Sierra Leone : Technical Assistance Report-Public Investment Management Assessment. (IMF Staff Country Reports; Country Report, 2021)
Sierra Leone has made significant strides to rebuild its public infrastructure after the devastating civil war, but the desperate infrastructure needs remain. At the end of the conflict in 2002, the country was left with virtually no infrastructure. Redevelopment of public infrastructure was ignited by the mining boom, which started in the late 2000s. Over the period 2008a-18, public investment averaged 6.5 percent of gross domestic product (GDP), which has translated into an estimated capital stock of about 65 percent in constant 2011 GDP. However, a level of public investment is still lower than neighboring countries by about one percentage point. The level of capital stock per capita is one of the lowest in the region, only slightly above that of Liberia. Some districts still have no paved roads, no electricity, and no water systems, almost 20 years after the war.